Analisis Perbandingan Emisi Gas Rumah Kaca dan Potensi Energi Listrik Antara Insinerasi dan Proses Biologi (Studi Kasus Pembangkit Listrik Tenaga Sampah Merah Putih) - Mulia Bakti, Rani; Susanto Joyosemito, Ibnu; Shanti Meilani, Sophia (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2024)
Solid waste disposal is one of the contributing sectors to greenhouse gas (GHG) emissions. Open burning of waste generates CO2, anaerobic decomposition of organic waste generates CH4, while composting activities and biological processes generate CO2, CH4, and N2O. Transportation to waste disposal facilities contributes to GHG emission as well. The aim of this study is to compare GHG emission and electrical energy generated from incineration and biological process. Calculation of estimated GHG emission in this study used the IPCC Tier 2 method with a combination of default data and local data such as data on the composition of waste for incineration compared to biological processes. The result indicated that incineration generated lower GHG emission compared to biological process. Higher electrical energy potential can be obtained from biological process, if most of CH4 is converted to electrical energy. PLTSA Merah Putih, which applied energy recovery from incineration, simultaneously convert heat to electrical energy and reduce GHG problem from CH4